KARAKTERISTIK POTENSIAL SIFAT MEKANIK, ANTIMIKROBA DAN BIODEGRADABLE BIOFOAM BERBAHAN ENCENG GONDOK (EICHHORNIA CRASSIPES) - Khoirunisa, Asiva; Zulfi, Erlin Maisatul; Safitri, Novita Aulia; Nisa’, Thufailah Khoirun; So’imah, Nur Faridatus; Yuliyanto, Eko (AGROINTEK, 2025)
The development of biodegradable foam, or Biofoam, utilizing water hyacinth cellulose and arrowroot starch, presents a promising alternative to the environmentally detrimental use of polystyrene foam. Water hyacinth, which proliferates extensively in the Semarang region and is often regarded as a parasitic species, boasts a significant cellulose and fiber content, quantified at 72.63%. This high cellulose content renders it a viable resource for the production of sustainable packaging materials, thereby addressing both environmental pollution and associated health risks posed by traditional polystyrene foam. This study aims to characterize the properties of the produced foam through a series of antimicrobial tests, tensile strength tests, and biodegradability assessments. The raw materials utilized include cellulose derived from water hyacinth stems, arrowroot starch, carboxymethyl cellulose (CMC), chitosan, and polyethylene glycol 400 (PEG 400). The result showed that Biofoam exhibits no bacterial growth, as determined by antimicrobial testing. The tensile strength test results were consistent with Synbra Technology standards, with tensile strength values ranging from 1.58 MPa to 2.63 MPa. Furthermore, Biofoam has successfully passed the biodegradability test, as evidenced by its degradation in soil using the soil burial test method, which is characterized by the physical transformation of Biofoam into a softer and more porous material. To improve the performance of the biofoam, further research is needed regarding its shape.